Genetic variability, heritability and genetic advance in shrunken-2 super-sweet corn (zea mays L. saccharata) populations (2019)
Inbred line development requires information on the nature and magnitude of genetic variability and transmissibility of desired trait in source populations. In this study, the level of genetic variability, heritability and genetic advance of thirteen agronomic and fresh yield traits among twelve shrunken-2 super-sweet corn populations were evaluated. Field experiments were conducted for two years in Ibadan, Nigeria using a randomised complete block design with three replicates. Estimates of genetic variability components, broad-sense heritability and genetic advance were computed for each trait. All the traits exhibited significant genotypic differences. Genotypic variance was significant for number of marketable cobs, yield of cobs, number of cobs, number of kernel rows, husk cover, ear height and days to anthesis, while environmental variance was significant for all the traits. Phenotypic coefficients of variation were higher than the corresponding genotypic coefficients of variation for all traits. Broad sense heritability ranged from 22.2% for anthesis-silking interval to 85.1% for husk cover. The genetic advance was high (32.7%) for husk cover, medium (12.0%) for yield of cobs and low for other traits. Genetic variability was present among the shrunken-2 super-sweet corn populations. Opportunities abound for further improvement of the populations and extraction of lines for hybrid seed production.